Analysis of Influencing Factors Regional Original Revenue (PAD) in The Provincial Government of DKI Jakarta - Febri Umar Doni (BPJP - STEI, 2018)
Abstract - The purpose of this study were (1) to Obtain empirical evidence of the influence of the Population against region income, (2) the effect of GRDP against the local revenue, (3) Obtain a picture of the effect of government spending on regional revenue, (4) describes the effect of Population, GRDP and government spending to regional revenue, (5) to analyze the influence of Total Population, GRDP and government expenditure to local revenue. In this sampling technique, Researchers used purposive sampling is done by taking the subject is not based on strata, random or region but is based to Obtain a sample of Jakarta's financial statements that will be Examined are the data of 2001 to 2014. The results Showed that (1) partially contained negative effect but not significant number of inhabitants of the regional income, (2) partially no positive effect but not significant GRDP against the local revenue, (3) partially contained positive and significant impact government expenditure of the local revenue, (4) there is simultaneously a positive and significant influence between Population, GRDP and government spending to regional revenue, (5) the influence of Total Population, GRDP and government spending to local revenue amounted to 92.7% while The remaining 7.3% is influenced by other factors outside the models of this study.